2017
DOI: 10.1002/tie.21896
|View full text |Cite
|
Sign up to set email alerts
|

Multinational Firms’ Motivations and Foreign Direct Investment Decisions: An Analysis of the Software and IT and Financial Services Sectors in the Irish Context

Abstract: This article focuses on the way greenfi eld foreign direct investment ( FDI ) in different sectors is infl uenced by locational characteristics and explores the role of policy in attracting and retaining foreign investment. We contribute to the literature by empirically investigating the investment motivations of multinational companies in the software and information technology ( IT ) and fi nancial services sectors in Ireland and those locational factors that contribute to the retention of FDI . The methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Note, however, that the motivation for FDI/ownership in the same country could be different depending on the industry. For example, Annan‐Diab and Fragiskos () found that, in the Irish context, availability of low‐cost skilled labor is the motivation for FDI/ownership in the case of software sector and low regulation in the case of financial services sector. In addition, we argue that intra‐firm trade in services is complementary to the stock of FDI in manufacturing, which is an indicator of FSA.…”
Section: Data and Regression Methodologymentioning
confidence: 99%
“…Note, however, that the motivation for FDI/ownership in the same country could be different depending on the industry. For example, Annan‐Diab and Fragiskos () found that, in the Irish context, availability of low‐cost skilled labor is the motivation for FDI/ownership in the case of software sector and low regulation in the case of financial services sector. In addition, we argue that intra‐firm trade in services is complementary to the stock of FDI in manufacturing, which is an indicator of FSA.…”
Section: Data and Regression Methodologymentioning
confidence: 99%
“…An important component of Ireland's success and its resurgence after the economic crisis at the turn of the millennium were the investments made in the national IS. These took the form of subsidies for high-tech investments, support for IT start-ups and establishment of institutions to support the strengthening of the knowledge economy (Annan-Diab & Filippaios, 2017;Coe, 1997). Ireland can be considered an example of strong and increasing integration into GVCs accompanied by high domestic investments in human capital and innovation.…”
Section: Explaining the Gvc Deepening And Innovation Strengthening Tr...mentioning
confidence: 99%
“…The proportion of employment in foreign‐owned companies as a percentage of total international trade‐related employment is the highest in the world and explains why Ireland is consistently ranked among the top five‐most economically globalized nations (EY/Economic Intelligence Unit Globalization Surveys, ). The United States is by far Ireland's largest source of FDI, with U.S. MNCs accounting for almost half of all foreign‐owned firms in the country (Annan‐Diab & Filippaios, ). Collectively, U.S. FDI in Ireland amounted to $343 billion in 2015.…”
Section: Research Contextmentioning
confidence: 99%